Southern Alps equilibrium line altitudes: four decades of observations show coherent glacier–climate responses and a rising snowline trend - Andrew M. Lorrey; Lauren Vargo; Heather Purdie; Brian Anderson; Nicolas J. Cullen; Pascal Sirguey; Andrew Mackintosh; Andrew Willsman; Gregor Macara; Warren Chinn (Journal of Glaciology, 2022)
An end of summer snowline (EOSS) photographic dataset for Aotearoa New Zealand contains over four decades of equilibrium line altitude (ELA) observations for more than 50 index glaciers. This dataset provides an opportunity to create a climatological ELA reference series that has several applications. Our work screened out EOSS sites that had low temporal coverage and also removed limited observations when the official survey did not take place. Snowline data from 41 of 50 glaciers in the EOSS dataset were retained and included in a normalised master snowline series that spans 1977–2020. Application of the regionally representative normalised master snowline series in monthly and seasonally resolved climate response function analyses showed consistently strong relationships with austral warm-season temperatures for land-based stations west of the Southern Alps and the central Tasman Sea. There is a trend towards higher regional snowlines since the 1990s that has been steepening in recent decades. If contemporary decadal normalised master snowline series trends are maintained, the average Southern Alps snowline elevation will be displaced at least 200 m higher than normal by the 2025–2034 decade. More frequent extremely high snowlines are expected to drive more extreme cumulative mass-balance losses that will reduce the glacierised area of Aotearoa New Zealand.